Rancang Bangun Alat Penghitung Harga pada Kertas yang Keluar dari Mesin Fotokopi ir6570 Berbasis Arduino Uno - Nurhidayat, Joko (2016)
Advances in technology at the moment has been proven as a means to facilitate a job, technological developments increasingly cangih strongly felt in the field of entrepreneurship and offices. then created the idea to create a tool that serves to calculate the nominal price of each paper coming out of the copier with counter method. The purpose of this tool is to simplify the pricing Copy and consumers also can know how much money they have to pay through the existing screen display. This study uses an Arduino UNO as the main controller, ultrasonic sensor as a detector of paper out of the machine as a copier and 20X4 LCD viewer screen results. There are four buttons are used to reset the paper, choose paper, reduce the price and increase the price. How to use this paper price calculator tool to turn the tool, then select the user presses the paper to determine what type of paper to be counted. From a total of 16 times experimental testing showed the percentage of testing counters on copier paper prices ir6570 with 0% error. Testing is done with different locations, from each point of testing is done 4 times with a percentage of 100% success.